A unique rectilinearly π-extended rhodamine dye with large Stokes shift and near-infrared fluorescence for bioimaging. Issue 77 (18th September 2017) - Liu, Chang; Jiao, Xiaojie; Wang, Qing; Huang, Kun; He, Song; Zhao, Liancheng; Zeng, Xianshun
Abstract : A NIR rhodamine fluorophore, TJ730, with a large Stokes shift over 110 nm has been developed. Using the dye as a platform, we have prepared two novel NIR probes for the detection of Cu 2+ as well as for cytoplasmic and lysosomal Cu 2+ imaging in living cells. Abstract : The synthesis of a novel rectilinearly π-extended rhodamine dye (TJ730 ) has been described. It exhibits NIR fluorescence emission with a Stokes shift of >110 nm.TJ730 and its ester derivative are cell permeable, have low cytotoxicity, are biocompatible, and can be directly used as NIR tracers for lysosome staining. UsingTJ730 as a precursor, two probes have been prepared for Cu 2+ .